The Effect Of Good Corporate Governance On Stock Returns Moderated By Intellectual Capital - Adhelia Widyasi; Novia Hadi Swarno; Fuji Wahyu Lestari; Mada Purwanto W.N (Al-Makki Publisher, 2024)
Good Corporate Governance is the management of a company that is transparent, accountable, responsible, fair, and considers all stakeholders. At the same time, intangible assets such as intellectual capital have a very important role in the shift to a knowledge-based economic orientation. Fund providers such as investors and creditors respond to the management of the company and the assets owned by the company in running the business. Changes in stock price, which is a component of stock return, will represent the response of fund providers. By analyzing the effect of intellectual capital on stock returns under the guidance of good corporate governance, this study seeks to generate empirical evidence. Companies in the financial sector listed between 2018 and 2022 on the Indonesia Stock Exchange serve as the study population. Purposive sampling was used to select 49 companies as research samples. Based on empirical evidence obtained from statistical analysis that has been carried out, all coefficients provide positive values, indicating that the movement of stock returns is in line with changes in Good Corporate Governance and intellectual capital. It can be concluded that the results of this study indicate that Good Corporate Governance affects stock returns. The effect of gcg on stock returns is strengthened by the role of intellectual capital, meaning that Good Corporate Governance will tend to have a greater influence on stock returns when the company has greater intellectual capital.